2003
DOI: 10.1002/ar.a.10075
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the pancreas in the house musk shrew (Suncus murinus), with special reference to the blood supply and innervation

Abstract: To examine the macroscopic structure, blood supply, and innervation of the pancreas in the house musk shrew (Suncus murinus), we performed gross anatomical dissection and whole-mount immunostaining of the autonomic nerve of Suncus pancreases based on neurofilament protein (NFP) immunoreactivity. The adult Suncus pancreas is clearly separated into right and left lobes that are not fused. The right lobe of the Suncus pancreas is located in the dorsum of the duodenum and to the right of the common bile duct indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…In the pN1 group, lymph node metastases characteristically arise in the pericholedochal area or the posterosuperior pancreaticoduodenal region, rather than around the hepatic artery (2,3). However, no feeding arteries are present around the pericholedochal lymph nodes and posterosuperior pancreaticoduodenal lymph nodes (PPLNs), although lymph nodes and lymphatic vessels generally exist along a feeding artery (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In the pN1 group, lymph node metastases characteristically arise in the pericholedochal area or the posterosuperior pancreaticoduodenal region, rather than around the hepatic artery (2,3). However, no feeding arteries are present around the pericholedochal lymph nodes and posterosuperior pancreaticoduodenal lymph nodes (PPLNs), although lymph nodes and lymphatic vessels generally exist along a feeding artery (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal, house musk shrew (Suncus murinus), which are common insectivores, has shown morphological characteristic very similar to those of humans than other species, i.e., mice, rats, and is useful as a model of human physiology and pathophysiology [20,[27][28][29]. According to our previous studies, the pancreases do not fuse as in humans or other species, and the two pancreases are located on the right and left of the common bile duct in Suncus murinus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand the human pancreas has a characteristic vascular system based on the peripancreatic arter- ies (Okahara et al, 2010), and compartmentalization of its blood supply may also be an obstacle to regeneration. The pancreas is usually formed by fusion of two primordia, which are known as the dorsal and ventral pancreatic buds, but in the Asian house shrew (Suncus murinus) the two buds do not merge (Yi et al, 2003). In organ cultures of rat pancreatic primordia, merging of the left and right lobes is not seen either (Spooner et al, 1970).…”
Section: Structure and Development Of The Pancreas And Pancreatic Isletsmentioning
confidence: 99%
“…In organ cultures of rat pancreatic primordia, merging of the left and right lobes is not seen either (Spooner et al, 1970). Anatomical comparison between the Asian house shrew and humans has shown that even if the two parts of the pancreas merge, the anatomy of the blood vessels, lymphatics, and nerves in the portions derived from the right and left primordia are different (Yi et al, 2003). In addition, pancreatic polypeptide (PP) cells are found in the right lobe, but are rare in the left lobe (Gersell et al, 1979).…”
Section: Structure and Development Of The Pancreas And Pancreatic Isletsmentioning
confidence: 99%